Splinter haemorrhages and brain infarcts as an unusual presentation of sarcoidosis. Issue 6 (30th June 2021) - Ayub, Shazeen; Hawari, Rand; Mahmood-Rao, Hamzah
Abstract : We present an interesting case of a healthy 47-year-old woman who presented to the acute take with symptoms of visual apraxia, splinter haemorrhages and extreme fatigue. This was a diagnostic challenge with other unusual features to this case, which includes brain infarcts on MRI, raised troponin and oeosinophilia. Naturally endocarditis was the top differential but this was ruled out by serial negative blood cultures and a negative transthoracic echocardiogram. Several medical specialties were involved and the initial working diagnosis was ANCA vasculitis (oeosinophilic granulomatosis with polyangiitis). Early administration of intravenous steroids clouded our judgement further and sarcoidosis was not thought as a possible differential. We illustrate the immensely challenging and complicated clinical course involving multiple specialties and investigations. In the end, a complete steroid wean was required to reach an accurate histological diagnosis.